Profissional Guidance: Report of experience with 3rd grade high school students - Leite, Lohana Oliveira; Viana, Paloma Lima; Silva, Carmem Virgínia Moraes da (Revista de Iniciação à Docência, 2024)
This report presents the results of a Professional Guidance practice in a public school in Vitória da Conquista, Bahia, carried out with students in the third year of high school, through a supervised undergraduate internship. Professional Guidance consists of a set of activities that aim to help students reflect on professional qualifications, the job market and opportunities. During the process, students experience activities that address self-knowledge and also provide information about possible paths after finishing high school. For this practice, the timetables of the Life Project discipline, which was developed to form the curriculum of all Brazilian schools, were used. This supervised internship process was built through studies in School/Educational Psychology and supported by the construction of knowledge from teaching in Psychology. The proposed methodology was through eight face-to-face meetings, lasting approximately sixty minutes, using questionnaires, dynamics, holding a conversation circle and creating material in the classroom. The results indicate that Professional Guidance equips students in a critical way, considering limits and possibilities of each one’s life context, regarding professional choice after the end of high school.